1986
DOI: 10.1080/15287398609530882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yohimbine on amitraz‐induced CNS depression and bradycardia in dogs

Abstract: Yohimbine was studied to examine its effectiveness in preventing central nervous system(CNS) depression and bradycardia induced by amitraz (N'-(2,4-dimethylphenyl)-N-[(2,4-dimethylphenyl-imino)-methyl]-N-methyl- methanimide). In control open-field activity experiments, the dogs showed high numbers of grid-line crossings in the first 5 min (exploratory phase), and subsequently low numbers of grid-line crossings (nonexploratory phase). An iv injection of amitraz (1 mg/kg) abolished both the exploratory and nonex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 7 publications
2
12
0
2
Order By: Relevance
“…The results obtained in this investigation showed that the administration of 4-aminopyridine, yohimbine or their combination was appropriate to reverse the xylazine-induced bradycardia, bradypnoea and ruminal atony. Similar results were also obtained in cattle 12 and in sheep 9 . At 0.88 mg/kg of xylazine, however, the combination of 4-aminopyridine and yohimbine produced only a slight improvement in the respiratory rates.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results obtained in this investigation showed that the administration of 4-aminopyridine, yohimbine or their combination was appropriate to reverse the xylazine-induced bradycardia, bradypnoea and ruminal atony. Similar results were also obtained in cattle 12 and in sheep 9 . At 0.88 mg/kg of xylazine, however, the combination of 4-aminopyridine and yohimbine produced only a slight improvement in the respiratory rates.…”
Section: Discussionsupporting
confidence: 78%
“…The antagonists, alone and in combination, significantly reduced the MST, which expresses the time required to gain full control of motor activities. Similar effects have been observed in sheep 9 , cattle 12 and llamas 21 . The reduction was greatest when yohimbine and 4-aminopyridine were combined, followed by 4-aminopyridine.…”
Section: Mst Mtrtsupporting
confidence: 70%
See 2 more Smart Citations
“…Autor para correspondência. II (FLÓRIO et al,1995) e da interação com α 2 -adrenoceptores de modo semelhante à xilazina e à clonidina (HSU & HOPPER , 1986).…”
Section: Introductionunclassified